Smoking Behavior and Human Capital Investment: Evidence from Indonesian Household - Albertus Girik Allo; Ni Made Sukartini; Endah Saptutyningsih (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2018)
This study aims at estimating the difference health and education performance between children with exposure to smoke and those who are not at home. An environment with the extreme smoke condition has adverse health effects. This study utilizes longitudinal data namely Indonesia Family Life Survey period 2007 and 2014 (IFLS4 and IFLS5). We use the Propensity Score Matching (PSM) method and the Average Treatment Effect on Treated (ATT). The health indicator is proxied by body mass index (BMI) and educational achievement proxied with children cognitive ability. The results show that children who grow in a household with active smoker tend to have lower health status and educational attainment compare to children who are not. This study recommends public policy for banning smoking in public areas as well as inside building such as house and office in Indonesia.DOI: 10.15408/sjie.v7i2.5793